Tuberculum Sellae Meningioma – Multiple Skullbase Approaches: Their Safety And Efficacy (Bangladesh Journal of Neurosurgery, 2022)
Background: Tuberculum sellae (T.S.) meningiomas accounts for 5–10% of all intracranial meningiomas. The primary goal of surgery is to improve or at least maintain visual function, but this objective poses a formidable surgical challenge, because of the risk of postoperative visual impairment. The aim of the present study was to evaluate outcome in TSM patients treated microsurgically using multiple skull base approaches such as transcranial approach and extended endonasal transsphenoidal approach.Materials and Methods: This is a retrospective study of 34 patients was aimed to observe the efficacy of the different common approaches by a single neurosurgeon. The approaches were minipterional approach, superciliary keyhole microscopic approach, superciliary keyhole endoscopic assisted approach, bifrontal basal approach and extended endoscopic endonasal approach. All the patients were evaluated preoperatively by visual field analysis and contrast MRI. Postoperative follow-up was done by visual field analysis and by contrast MRI or contrast CT scan of brain.Result: Through transcranial surgery vision improved in 86.20%, static in 10.34% and deteriorated vision in 03.45%. Through transsphenoidal surgery vision improved in 80%, static in 20% and deteriorated in 0%. Through transcranial microscopic approaches (minipterional, minibifrontal basal, superciliary keyhole microscopic) gross total removal was done in 58.82%, near total in 10.34% and partial removal in 03.45%. Through transcranial/superciliary keyhole endoscopic assisted approach, gross total removal was done in 80% and near total in 20%. Through transsphenoidal approach gross total removal was done in 60%, near total in 20% and partial removal in 20%.Conclusion: Now a days endoscopic assisted key hole superciliary mini craniotomy for resection of tuberculum sellae meningioma is commonly used because of less morbidity and good visual outcome and this can be done without microscopic set up. The endonasal route is preferred for removal of T.S. meningioma when they are mostly sellar and directing towards third ventricle. The major limitation of this approach is a narrow surgical corridor. The gross total removal was better achieved with minibifrontal basal and minipterional craniotomy.Bang. J Neurosurgery 2022; 11(2): 80-88